Bibliometric Analysis: Forest Fire Controlling Policy in Indonesia - Mutia Rahmah (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to identify and analyze the intensity of research developments with the topic of forest fire controlling policy in Indonesia in the last five years from 2017 to 2021 through bibliometric analysis. The research method uses a literature review with data collection through the publish or perish software from the google scholar database with the keywords “forest fire Indonesia,” “forest fire management, Indonesia,” forest fire control, Indonesia,” and “forest fire policy, Indonesia.” Data analysis using the VOSviewer application. The results showed 154 journal articles discussing forest fire controlling policy in Indonesia between 2017 and 2021 accessed on December 18, 2021. The term